Impact of the COVID-19 pandemic and associated lockdown measures on the management, health, and behavior of the cystic fibrosis population in France during 2020 (MUCONFIN) - Oubaya, Nadia; Pombet, Thibaud; Delestrain, Celine; Remus, Natascha; Douvry, Benoit; Grenet, Dominique; Corvol, Harriet; Thouvenin, Guillaume; Prulière-Escabasse, Virginie; Mounir, Hakima; Argoud, Dominique; Fretigne, Cédric; et al. (Frontiers in Public Health, 2022)
Background Most of the studies on cystic fibrosis (CF) focused on SARS-CoV-2 prevalence and suggested a low incidence of infection in this population. We aimed to assess the impact of the pandemic and related lockdown measures implemented in May 2020 in response to the first wave of SARS-CoV-2 infection on healthcare access, health, and behavior in CF patients. Methods A national questionnaire opened online from May 15th, 2020 to June 11th, 2020 was completed by 751 CF-patients, aged 14 years and over. It comprised questions about access to healthcare, anxiety and depression, smoking, alcohol, drug and psychotropic drug consumption, adherence to CF treatment, and constraints. A semi-structured comprehensive interview was performed no later than 1 month after the end of the lockdown in 16 CF-patients. Results The mean age of the population was 28.0 [interquartile range (IQR) 20.0–37.0] years old. More than 75% of in-person consultations scheduled during the lockdown were canceled. Alternatively, 27% were postponed, and telehealth consultations were proposed and accepted in almost 40% of cases. More than 75% of the scheduled physiotherapy sessions were canceled and replaced mainly by self-drainage. Annual follow-up clinic visits were consistently postponed whereas required hospitalizations at CF centers for exacerbation were maintained in most cases. While 43.2% CF-patients had signs of anxiety, 51.0% presented symptoms of depression, both associated with increased use of psychotic medications and inversely correlated to COVID-19 prevalence. Among the lower and lower middle classes, very little medical information was obtained or requested by the patient, participation to sports or other activities was low, while excessive home confinement and isolation were more frequent. In contrast, in the upper middle and upper classes, individuals solicitated help to their CF centre, had more physical activities, and maintained contact with friends or families. Conclusion The first lockdown in France had only minimal impact on the management care of CF-patients but was associated with increased symptoms of anxiety and depression, together with behavioral changes that varied with social class. Trial registration NCT04463628.